2018
DOI: 10.1016/j.amepre.2018.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Community Education and Engagement in Family Planning: Updated Systematic Review

Abstract: Context: Community education and engagement are important for informing family planning projects. The objective of this study was to update two prior systematic reviews assessing the impact of community education and engagement interventions on family planning outcomes. Evidence acquisition: Sixteen electronic databases were searched for studies relevant to a priori determined inclusion/exclusion criteria in high development settings, published from March 2011 through April 2016, updating two reviews that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 45 publications
(193 reference statements)
0
18
0
2
Order By: Relevance
“…After duplicates were removed in Endnote, 3,735 articles remained for title and abstract screening. The reference lists of eight relevant reviews (22)(23)(24)(25)(26)(27)(28)(29) identified in the title and abstract screening were additionally screened, but no priorly unknown relevant study was found. From this initial screening phase, 85 articles were included in the full-text screening.…”
Section: Resultsmentioning
confidence: 99%
“…After duplicates were removed in Endnote, 3,735 articles remained for title and abstract screening. The reference lists of eight relevant reviews (22)(23)(24)(25)(26)(27)(28)(29) identified in the title and abstract screening were additionally screened, but no priorly unknown relevant study was found. From this initial screening phase, 85 articles were included in the full-text screening.…”
Section: Resultsmentioning
confidence: 99%
“…Así, por ejemplo, la asistencia formativa que deriva de los ámbitos de la salud mental y la pediatría, también incluye la comunicación familiar como una herramienta necesaria para obtener beneficios positivos mediante la navegación compartida, etc. (Sharma, Frederiksen, Malcolm, Rollison y Carter, 2018).…”
Section: Preocupaciones Y Necesidades De Las Familias Para Educar En Las Redes Socialesunclassified
“…Pemberian KIE bisa dilakukan melalui metode pendidikan komunitas atau disebut sebagai community education. Sebuah kajian ilmiah mengenai KIE program KB menjelaskan bahwa pendekatan community education merupakan sebuah pendekatan yang positif dalam mentransfer pengetahuan KB dan didukung media promosi, seperti media massa, situs jejaring (website), penjelasan menggunakan selebaran (leaflet) atau lembar balik, dan juga pendekatan secara interpersonal (Sharma, Frederiksen, Malcolm, Rollison, & Carter, 2018). Informasi KB yang diterima dengan baik oleh akseptor KB akan membantu meningkatkan kewaspadaan dalam menghadapi efek samping dan mengurangi putus-pakai pada pemakaian alat kontrasepsi (Bappenas RI, 2010).…”
Section: Pembahasanunclassified